Expression of the Recombinant Protein Substrate for Detection of the Endopeptidase Activity of Botulinum Neurotoxin Serotype B - Anh, Le Phan; Phuong, Vu Thi; Yen, Pham Bao; Nhung, Le Thi Hong; Nghia, Phan Tuan; Loan, Nguyen Thi Hong (VNU Journal of Science: Natural Sciences and Technology, 2024)
Botulinum neurotoxins (BoNTs) produced by Clostridium botulinum are metalloproteases. Based on structural differences and substrate specificity, BoNTs are classified into 8 serotypes from A to H. Identification of the endopeptidase activity of BoNTs is the basis for BoNT detection. In this study, a recombinant gene encoding for the substrate of the BoNT serotype (BoNT/B) was successfully cloned and expressed in E. coli BL21(DE3) using a pET28CYL1 vector. At the N-terminus of the designed recombinant protein, there was 6 ´ His tag along with an enhanced cyan fluorescent protein. The C-terminus held an enhanced yellow fluorescent protein, while a peptide with amino acid sequences spanning from 60 to 94 residues of VAMP2 (a natural substrate of BoNT/B) was positioned in the midsection. The whole construct was called 6 ´ His-CFP-VAMP2(60-94)-YFP, with a molecular weight of approximately 60.1 kDa. The substrate protein exhibited a high level of expression in the soluble fraction of E. coli BL21(DE3), which was purified via Ni-affinity chromatography to electrophoretic homogeneity. The extracellular fluid of C. botulinum serotype B (crude BoNT/B) cleaved the recombinant protein to generate two smaller protein fragments that are consistent with theoretical calculations. Crude BoNT/B required the presence of dithiothreitol (DTT) for substrate proteolytic cleavage, but it was inhibited by ethylene diamine tetraacetic acid (EDTA).